An Incidental Uptake of 18F-Choline in Paraganglioma. (10th September 2021) - Castello, Angelo; Zuccotti, Giulia; Bonatto, Elena; Florimonte, Luigia; Castellani, Massimo
Abstract: We present a case of carotid glomus paraganglioma incidentally detected using 18 F-choline PET/CT in a 63-year-old man with prostate cancer. 18 F-choline PET/CT scan demonstrated a small area of 18 F-choline uptake (SUVmax, 2.3) in the right parapharyngeal space of the neck, later diagnosed as paraganglioma with low proliferation index. 18 F-choline PET/CT may represent a valid alternative for studying paraganglioma when either 18 F-DOPA or 68 Ga-SSA are not available.